2022
DOI: 10.3390/ph15111342
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Methyldopa and Baicalein or Scutellaria baicalensis Roots Extract on Blood Pressure, Heart Rate, and Expression of Inflammatory and Vascular Disease-Related Factors in Spontaneously Hypertensive Pregnant Rats

Abstract: The aim of the study was to investigate the effect of baicalein or Scutellaria baicalensis root extract interaction with methyldopa in pregnant spontaneously hypertensive rats (SHR) at the pharmacodynamic, molecular, and biochemical levels. The rats, after confirming pregnancy, received baicalein (200 mg/kg/day, p.o.) and extract (1000 mg/kg/day, p.o.), in combination with methyldopa (400 mg/kg/day; p.o.), for 14 consecutive days, 1 h before blood pressure and heart rate measurements. In the heart and placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 97 publications
2
7
0
Order By: Relevance
“…The optimal amount provides the highest absorption value at 550 nm within the linear range (0.4-100) µ /mL for the dye in Fig. (3) and Fig ( 4), so a concentration of 100 µ/mL was adopted as the highest value subjected to Beer's law and used in the subsequent experiments. While the second stage included several experiments to examine the possibility of bleaching the dye in an acidic or basic medium, each separately, by adding a fixed amount of 1 mL of hydrochloric acid at a concentration of 1 M and 1 mL of sodium hydroxide at a concentration of 1 M, followed by adding a fixed amount of oxidizing agents, then adding the optimal amount of the dye, as the experiments showed that a dropping of the dye occurred with the increase in the amount of the oxidizing agent in the acidic medium, while in the alkaline medium was non-quantitative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal amount provides the highest absorption value at 550 nm within the linear range (0.4-100) µ /mL for the dye in Fig. (3) and Fig ( 4), so a concentration of 100 µ/mL was adopted as the highest value subjected to Beer's law and used in the subsequent experiments. While the second stage included several experiments to examine the possibility of bleaching the dye in an acidic or basic medium, each separately, by adding a fixed amount of 1 mL of hydrochloric acid at a concentration of 1 M and 1 mL of sodium hydroxide at a concentration of 1 M, followed by adding a fixed amount of oxidizing agents, then adding the optimal amount of the dye, as the experiments showed that a dropping of the dye occurred with the increase in the amount of the oxidizing agent in the acidic medium, while in the alkaline medium was non-quantitative.…”
Section: Resultsmentioning
confidence: 99%
“…1. psychiatric disorders, including schizophrenia and addiction [3]. It is used to treat preeclampsia and gestational hypertension during pregnancy, as well as hypertensionrelated emergencies such as hypertensive encephalopathy and acute heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, STZ was chosen as the agent to induce diabetes due to its cytotoxic effect on pancreatic cells [39]. STZ's ability to produce excessive reactive oxygen species (ROS), carbonium ions (CH3+), and alkali leads to the selective destruction of pancreatic cells without causing harm to other cell types [39].…”
Section: Impact Of Baicalin On the Levels Of Blood Glucose Insulin He...mentioning
confidence: 99%
“…In this study, STZ was chosen as the agent to induce diabetes due to its cytotoxic effect on pancreatic cells [39]. STZ's ability to produce excessive reactive oxygen species (ROS), carbonium ions (CH3+), and alkali leads to the selective destruction of pancreatic cells without causing harm to other cell types [39]. The injection of streptozotocin at a dose of 40 mg/kg resulted in partial death of pancreatic cells, replicating the characteristics of type 2 diabetes [40].…”
Section: Impact Of Baicalin On the Levels Of Blood Glucose Insulin He...mentioning
confidence: 99%
“…Baicalein (BCL), a flavonoid extracted from Scutellaria baicalensis Georgi , is known for its antitumor effect in various malignancies. It was reported that BCL reduced blood pressure by regulating inflammatory and vascular disease-related factors in hypertensive pregnant rats [ 35 ]. Also, BCL was reported to protect liver and kidney function by inhibiting apoptosis in a PE model [ 36 ].…”
Section: Introductionmentioning
confidence: 99%